Pengembangan Lembar Kerja Mahasiswa Untuk Menunjang Kegiatan Laboratorium Virtual Pada Materi Radioaktivitas Alamiah - Annisa Citra Vivany; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2018)
Based on the observations, data from student's response shows to the nuclear physics lecture is that the nuclear physics material is an abstract material so it needs visualization in the learning. The facts found that in the learning process of nuclear physics material there is no virtual laboratory activities yet. The virtual laboratory is needed by the students in visualizing the abstract material of nuclear physics. This research is developing a student’s worksheet on the radioactivity material to support the activity of virtual laboratory applying PhET simulation. This study aims to see the advisability of validity and practicality of the student’s worksheet products developed. Research type is research and development (R & D) by applying the ADDIE model with stage analyze, design, development, implementation and evaluation. Using the research instrument with the form of validation and practicality questionnaire are obtained data of the average value of student’s worksheet validation is 91  with the category is very valid and the average value of student’s worksheet practice is 88  for lecturers and 89  for students with category very practice. The results of this study indicate that the student’s worksheet developed are valid and practical for use in supporting virtual lab activities.   Keywords : LKM, virtual laboratory , Physics Education Technology